Is Human Chorionic Gonadotropin Trigger Beneficial for Natural Cycle Frozen-Thawed Embryo Transfer? - Gao, Dan-Dan; Li, Li; Zhang, Yi; Wang, Xiao-Xuan; Song, Jing-Yan; Sun, Zhen-Gao (Frontiers in Medicine, 2021)
Objective The aim of this study is to investigate, in ovulatory patients, whether there is a difference in reproductive outcomes following frozen-thawed embryo transfer (FET) in natural cycles (NC) compared to modified natural cycles (mNC). Methods This retrospective cohort study, performed at the public tertiary fertility clinic, involved all infertile patients undergoing endometrial preparation prior to FET in NC and mNC from January, 2017 to November, 2020. 1162 patients were divided into two groups: mNC group (n = 248) had FET in a NC after ovulation triggering with human chorionic gonadotropin (hCG); NC group (n = 914) had FET in a NC after spontaneous ovulation were observed. The primary outcome was live birth rate. All pregnancy outcomes were analyzed by propensity score matching (PSM) and multivariable logistic regression analyses. Results The NC group showed a higher live birth rate [344/914 (37.6%) vs. 68/248 (27.4%), P=0.003; 87/240 (36.3%) vs. 66/240 (27.5%), P=0.040] than the mNC group before and after PSM analysis. Multivariable analysis also showed mNC to be associated with a decreased likelihood of live birth compared with NC [odds ratio (OR) 95% confidence interval (CI) 0.71 (0.51 to 0.98), P=0.039]. Conclusion For women with regular menstrual cycles, NC-FET may have a higher chance of live birth than that in the mNC-FET cycles. As a consequence, it's critical to avoid hCG triggering as much as possible when FETs utilize a natural cycle strategy for endometrial preparation. Nevertheless, further more well-designed randomized clinical trials are still needed to determine this finding.